Shreds of matter : Cormac McCarthy and the concept of nature - Greve, Julius (Dartmouth College Press, 2018)
"Julius Greve offers a nuanced and innovative take on the writer's ostensible localism and the ecocentric perspective on the world that is assumed by most critics. In opposing both the standard interpretations of McCarthy's novels as either critical of persisting American ideologies--manifest destiny and imperialism--or of the ways in which humanity has wasted Planet Earth, Greve emphasizes the author's interest in the history of science and in the mythographical developments of religious discourse."-- Provided by publisher.
Keywords: McCarthy, Cormac, -- 1933-2023 -- Criticism and interpretation.; McCarthy, Cormac, -- 1933-; Ecology in literature.; LITERARY CRITICISM -- American -- General.; Ecology in literature; Electronic books.; Criticism, interpretation, etc.